Analisis Keragaman Genetik Andaliman (Zanthoxylum acanthopodium DC.)Sumatera Utara Menggunakan Marka RAPD (Random Amplified Polymorphic DNA) - Ayu Oshin Yap Sinaga; Lollie Agustina P. Putri; Luthfi Aziz M. Siregar (Universitas Sumatera Utara, 2015)
The aim of the research was to analyze the genetic diversity of the endemic andaliman inNorth Sumatera based on RAPD markers. A total of 30 accessions andaliman originated fromthe various region in North Sumatera, i.e.: Dairi, Karo Highland, Simalungun. The RAPDanalyse was used with 3 random primer: OPH-06, OPC-12 and OPN-03. These three primersshowed 32 bands, on which 31 were polymorphic (95.23%). Further genetic diversitycoefficient and the filogenetic dendogram were obtained using the Darwin 5.05 software. Theresults showed that 30 accessions of andaliman were clustered in three groups. Each groupconsisted of the accessions of three regions from different altitudes. There were 30 accessionsof three regions studied showed a high genetic diversity.Keywords: Andaliman, genetic diversity, random amplified polymorphic DNA